2011
DOI: 10.1007/s00572-010-0352-0
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal symbiosis elicits proteome responses opposite of P-starvation in SO4 grapevine rootstock upon root colonisation with two Glomus species

Abstract: Although plant biotisation with arbuscular mycorrhizal fungi (AMF) is a promising strategy for improving plant health, a better knowledge regarding the molecular mechanisms involved is required. In this context, we sought to analyse the root proteome of grapevine rootstock Selection Oppenheim 4 (SO4) upon colonisation with two AMF. As expected, AMF colonisation stimulates plant biomass. At the proteome level, changes in protein amounts due to AMF colonisation resulted in 39 differentially accumulated two-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 87 publications
3
16
0
Order By: Relevance
“…It has been shown that mycorrhizal plants may have fewer and shorter roots than non-mycorrhizal plants, since extraradicular AMF mycelium increases the volume of soil explored by the plant root system, allowing higher water and nutrient uptake (Locatelli et al, 2002). Therefore, these results confirm the ability of AMF to benefit plant growth, and the increase in shoot and root biomass is consistent with previous studies with grapevine rootstocks (Dalla Costa et al, 2010;Anzanello et al, 2011;Cangahuala-Inocente et al, 2011) or with other plant species (Lovato et al, 2006;Farzaneh et al, 2011;Cavagnaro et al, 2012;Evelin et al, 2012;Mohandas, 2012;Steinkellner et al, 2012). Anzanello et al (2011) detected an increase in shoot and root biomass in SO4 and P1103 rootstocks inoculated with AMF, and Dalla Costa et al (2010) also showed an increase in shoot biomass in SO4 rootstock inoculated with AMF.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…It has been shown that mycorrhizal plants may have fewer and shorter roots than non-mycorrhizal plants, since extraradicular AMF mycelium increases the volume of soil explored by the plant root system, allowing higher water and nutrient uptake (Locatelli et al, 2002). Therefore, these results confirm the ability of AMF to benefit plant growth, and the increase in shoot and root biomass is consistent with previous studies with grapevine rootstocks (Dalla Costa et al, 2010;Anzanello et al, 2011;Cangahuala-Inocente et al, 2011) or with other plant species (Lovato et al, 2006;Farzaneh et al, 2011;Cavagnaro et al, 2012;Evelin et al, 2012;Mohandas, 2012;Steinkellner et al, 2012). Anzanello et al (2011) detected an increase in shoot and root biomass in SO4 and P1103 rootstocks inoculated with AMF, and Dalla Costa et al (2010) also showed an increase in shoot biomass in SO4 rootstock inoculated with AMF.…”
Section: Resultssupporting
confidence: 90%
“…Among the grapevine rootstocks available in southern Brazil, the SO4 rootstock (Vitis berlandieri × V. riparia) was commonly used in grapevine production due to its adaptability to different types of soils and climate, as well as to its vigour, which ensures high yield and fruit quality. However, SO4 was replaced, due to its susceptibility to FOH (Andrade et al, 1993;Dalla Costa et al, 2010;Cangahuala-Inocente et al, 2011), by Paulsen 1103, R99 and R110 (V. berlandieri × V. rupestris), and VR043-43 (V. vinifera × V. rotundifolia) grapevine rootstocks, resistant to FOH, which are currently the most recommended rootstocks in southern Brazil (Sônego et al, 2005;Souza et al, 2013). These rootstocks have low root development, and consequently low yield, but they have a long production cycle (Dalla Costa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that work both G. mosseae and G. irregulare were shown to induce modifications in the display of 39 proteins, 25 of which were identified by matrix assisted laser desorption ionization-time of flight (MALDI-TOF) spectrometry. These identifications showed that several proteins with decreased expression in mycorrhizal plants are involved in response to hypoxia, and downregulation of proteins involved in production of free radical and antioxidant defenses was also observed [51].…”
Section: Phenol Extraction Of Proteinsmentioning
confidence: 93%
“…More recently, phenol extraction of proteins was shown to be very efficient also for recalcitrant tissues, such as grapevine roots [51]. In that work both G. mosseae and G. irregulare were shown to induce modifications in the display of 39 proteins, 25 of which were identified by matrix assisted laser desorption ionization-time of flight (MALDI-TOF) spectrometry.…”
Section: Phenol Extraction Of Proteinsmentioning
confidence: 99%